THE IMPACT OF ENGLISH AS AN INTERNATIONAL LANGUAGE ON ENGLISH LANGUAGE TEACHING IN INDONESIA - Gunantar, Devy Angga (Language Circle: Journal of Language and Literature, 2016)
This study aims to analyze the impact of English as an International Language on English Language Teaching in Indonesia. In analyzing the impact of English as an International Language, the writer analyzed how cultural issues are presented in English textbooks, and revealed the teachersâ perspective about learning English in Indonesia. The data were collected from SMP N 1 Wiradesa, Pekalongan. The study revealed that the English textbooks in SMP N 1 Wiradesa mostly represented the local cultures. Some teachers of SMP N 1 Wiradesa preferred textbooks that deal with the life and culture of various countries around the world and the rest of them chose the content that deals with local cultures. Textbooks have played a very important role in the teaching and learning process. This study shows that, basically, local cultural content has become the purpose of EFL teaching as seen from the textbooks but some teachers still believe that foreign cultures are the suitable target of learning English.